Axial Spondyloarthritis in the Era of Precision Medicine: Biomarkers, Microbiota, and Multimodal Therapy - Kopeć, Karolina; Bartoszek , Aleksandra; Adamiuk , Julia; Marut, Agnieszka; Biskup, Marta; Misiuk, Jagoda; Skuba, Adriana; Załuska, Katarzyna; Śmigiel , Wiktoria; Świdniak, Agnieszka (Quality in Sport, 2025)
Introduction and Purpose Axial spondyloarthritis (axSpA) is a chronic inflammatory rheumatic disease affecting the axial skeleton. It includes both radiographic (r-axSpA) and non-radiographic (nr-axSpA) forms. This study aims to compare the clinical characteristics, disease burden, and treatment outcomes of r-axSpA and nr-axSpA and evaluate the role of biomarkers, microbiota, and physical therapy in disease management. Materials and Methods A systematic review of the literature was conducted, analyzing clinical studies comparing r-axSpA and nr-axSpA, focusing on disease activity indices (ASDAS, BASDAI), inflammatory markers, microbiome alterations, and treatment approaches, including NSAIDs, TNFi, IL-17 inhibitors, and JAK inhibitors. The impact of exercise programs on disease progression was also assessed. Results Patients with r-axSpA had longer disease duration, higher CRP levels, and more structural damage, while those with nr-axSpA had a higher prevalence of peripheral manifestations. ASDAS was found to be superior to BASDAI for monitoring disease activity. Biologic therapies, particularly TNFi and IL-17 inhibitors, showed efficacy in symptom control. Physical therapy, especially aquatic and workplace-home combined exercises, significantly improved mobility, quality of life, and pulmonary function. Conclusion AxSpA requires a multidisciplinary approach combining pharmacological treatment, exercise, and lifestyle modifications. Biologic drugs remain the mainstay of treatment for refractory cases, while ASDAS is the preferred disease activity measure. Future research should explore microbiome-targeted therapies and personalized treatment strategies.